Potential Alternatives for Palestinian Trade : Developing the Rafah Trade Corridor - World Bank (Washington, DC, 2016)
This paper covers the following four key issues: (i) Palestinian trade against the background of global trade expansion; (ii) trade logistics and performance using Egyptian gateways; (iii) establishing the border terminal operations and transit protocols; and (iv) conclusions and next steps. The study point out that the success of the Rafah corridor is dependent on establishing practices and procedures which, while sensitive to legitimate security and economic concerns and minimizing risks, are appropriate and focused on facilitating efficient and reliable trade. It suggests that the development of the Rafah corridor take a phased approach beginning with specially arranged demonstration shipments to jump start operations and then expanding these activities as systems and procedures are instituted and improved. The report believes that using Rafah as a trade corridor to ship goods from Gaza to Egypt's efficient and privately managed container terminal at the entrance to the Suez Canal and to Cairo International Airport can provide competitive trade logistics in terms of performance and at a cost generally equivalent to or less than Israel's ports and airports.